Effects of paratuberculosis on Friesian cattle carcass weight and age at culling - Vázquez, P.; Garrido, J. M.; Juste, R. A. (Spanish Journal of Agricultural Research, 2012)
Bovine paratuberculosis (PTB) causes major economic losses to dairy farmers because of decreased milk production, poor body condition, weight loss and early culling. The aim of this study was to evaluate the effect of Mycobacterium avium subspecies paratuberculosis (MAP) infection on carcass weight and age at slaughter in Friesian cattle. A total of 1,014 adult cows slaughtered at two local abattoirs in the Basque Country were included in this study. MAP infection was determined by different methods: indirect ELISA on blood samples, detection of MAP in tissues by culture and real time PCR (rtPCR), and histopathological examination. Serial and parallel interpretations of these methods were also considered for setting the upper and lower infection rates. MAP infection was confirmed by at least one test in 58.9% of animals. Most infected cows were detected by histopathology (46.9%) and rtPCR (29.6%). Overall estimates of carcass mean weight losses ranged from 3.7% for cases identified by the presence of microscopic specific PTB inflammatory lesions to 12.4% for cases with positive results in the paratuberculosis antibody ELISA test. Isolation of high bacterial loads in tissues and occurrence of diffuse granulomatous enteritis were associated with the highest weight loses, 22.2% and 26.0% respectively. The life expectancy of seropositive cows and those showing diffuse lesions was reduced by nearly one year compared to that of non-infected ones. Our results provide consistent evidences of PTB effect on the reduction of slaughter weight and lifespan of dairy cows, which could be considered as surrogates of clinical disease.